2022
DOI: 10.1038/s42003-022-03043-2
|View full text |Cite
|
Sign up to set email alerts
|

Inter-individual variability amplified through breeding reveals control of reward-related action strategies by Melanocortin-4 Receptor in the dorsomedial striatum

Abstract: In day-to-day life, we often must choose between pursuing familiar behaviors or adjusting behaviors when new strategies might be more fruitful. The dorsomedial striatum (DMS) is indispensable for arbitrating between old and new action strategies. To uncover molecular mechanisms, we trained mice to generate nose poke responses for food, then uncoupled the predictive relationship between one action and its outcome. We then bred the mice that failed to rapidly modify responding. This breeding created offspring wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…For instance, inter-individual differences in baseline anxiety-like behavior (ALB) in Wistar rats affected subsequent amygdala kindling in that only rats with increased baseline ALB before kindling exhibited a lasting increase in ALB after kindling ( Adamec and Shallow, 2000 ). Similar observations have been reported for various other behavioral phenotypes ( Pitychoutis et al, 2011 ; Armario and Nadal, 2013 ; Freund et al, 2013 ; Theilmann et al, 2016 ; Dellu-Hagedorn et al, 2018 ; Allen et al, 2022 ). Thus, as in humans, the development of pathologies in laboratory rodents is related to individual differences determining either vulnerability or resilience.…”
Section: Variation In Disease Susceptibilitysupporting
confidence: 88%
See 1 more Smart Citation
“…For instance, inter-individual differences in baseline anxiety-like behavior (ALB) in Wistar rats affected subsequent amygdala kindling in that only rats with increased baseline ALB before kindling exhibited a lasting increase in ALB after kindling ( Adamec and Shallow, 2000 ). Similar observations have been reported for various other behavioral phenotypes ( Pitychoutis et al, 2011 ; Armario and Nadal, 2013 ; Freund et al, 2013 ; Theilmann et al, 2016 ; Dellu-Hagedorn et al, 2018 ; Allen et al, 2022 ). Thus, as in humans, the development of pathologies in laboratory rodents is related to individual differences determining either vulnerability or resilience.…”
Section: Variation In Disease Susceptibilitysupporting
confidence: 88%
“…It is noteworthy that stress may also play a role in inter-individual variability in epilepsy ( Jhaveri et al, 2023 ). As in our study in the kindling model of DRE ( Ebert and Löscher, 1999 ), selective breeding has been used to examine the potential mechanisms of inter-individual variability in models of psychiatric disorders ( Allen et al, 2022 ).…”
Section: Insights From Stress-induced Models Of Depression In Rodentsmentioning
confidence: 99%
“…In operant conditioning procedures, young rats favor habit-based response strategies even under conditions that induce goal-seeking behavior in adults, suggesting that young organisms are more prone to use habit-based action strategies [ 52 ]. Allen, Heaton [ 53 ] capitalized on this propensity to identify highly habit-prone mice for later selective breeding for habit bias. Relatedly, Moin Afshar, Keip [ 54 ] revealed that the capacity for goal-based action strategies develops across juvenile and adolescent development, crystalizing only in young adulthood [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intra-VTA infusion of the selective MC3R agonist γ-MSH, on the contrary, increases responding for sucrose under a progressive ratio schedule of reinforcement [ 343 ]. MC4R in the dorsomedial striatum appears to propel reward-seeking behavior [ 344 ].…”
Section: The Role Of Melanocortins In Motivational and Hedonic Behaviormentioning
confidence: 99%